THE EFFECT OF FINANCIAL INCLUSION ON STABILITY OF SHARIA BANKING IN INDONESIA - Pindy Kurnia Virda; Estu Widarwati; Nunik Nurmalasari (STIESA Press, 2019)
Financial inclusion began as a consequence of 2008 crisis. This is because there are still many people who are classified as unbanked. Indonesia is a country with a high unbanked population. Providing an ease of banking access, unbanked community can affect the stability of sharia banking as one of the formal financial institutions. The objective of this research is to find out the effect of financial inclusion on stability of sharia banking in Indonesia. This research is a quantitative research using one dependent variable that is Non Performing Financing as proxy of syariah banking stability and two independent variable that is SMEs Small Medium Enterprises Loan as proxy of financial inclusion and variable of deposit. The data used in this research is obtained from the Annual Report of Banking Company Publication from each company webpage. Purposive Sampling method used in this research is 5 syariah bank in Indonesia in 2011-2016, total observation unit is 30. The type of data used is secondary data, which is a combination of time series and cross section. The statistical tools used are Eviews Version 9 and SPSS 22. The results showed that the deposit variable as a proxy of financial inclusion affects the financial system stability and financing of umkm has no effect on the stability of the financial system. The coefficient of determination that shows the influence of deposits and financing umkm to the stability of the financial system by 39.25%, while the remaining 60.75% is explained by other variables outside the model.